2014
DOI: 10.1007/s12032-014-0205-3
|View full text |Cite
|
Sign up to set email alerts
|

Elevated level of microRNA-21 in the serum of patients with colorectal cancer

Abstract: In patients with colorectal cancer, circulating micro RNA-21 (miR-21) is overexpressed and may act as a potential diagnostic and prognostic biomarker. In the present study, serum miR-21 level was determined in patients with colorectal cancer and control subjects in an attempt to explore its potential clinical diagnostic and prognostic value. Serum levels of miR-21 were measured in 40 patients with colorectal adenocarcinoma and 40 control subjects using a quantitative reverse-transcriptase polymerase chain reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 22 publications
4
23
0
Order By: Relevance
“…Furthermore, we examined the association between exosomal miR-21 levels and clinicopathological factors, and demonstrated that high levels of miR-21 expression have a significant association with liver metastasis and TNM stage. Basati et al [26] also reported that plasma miR-21 levels are associated with tumor stage progression, thereby supporting our results.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, we examined the association between exosomal miR-21 levels and clinicopathological factors, and demonstrated that high levels of miR-21 expression have a significant association with liver metastasis and TNM stage. Basati et al [26] also reported that plasma miR-21 levels are associated with tumor stage progression, thereby supporting our results.…”
Section: Discussionsupporting
confidence: 92%
“…Recently, several papers have reported the usefulness of plasma/serum miR-21 levels as a biomarker for diagnosis in CRC patients [23,24,25,26,27,28]. However, the clinical significance of plasma/serum miRNA as a biomarker for diagnosis is still controversial, and some papers have indicated that serological miR-21 does not have any impact on diagnosis in CRC patients [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…The differential expression of hsa-miR-21-3p, hsa-miR-150-5p, hsa-miR-1290 and hsa-miR-623 was validated using RT-qPCR. Previously, hsa-miR-21-3p was demonstrated to exhibit oncogenic functions in osteosarcoma, breast cancer and colorectal cancer (14)(15)(16). The results of the present study demonstrated that hsa-miR-21-3p expression was increased in chordoma and may regulate invasion and metastasis, and hsa-miR-150-5p is overexpressed in chordoma tissues which acts as an oncogene.…”
Section: Discussionsupporting
confidence: 60%
“…As a result, circulating miRNAs aim to screen for the detection of CRC should have an efficiency at delineating the earlier lesions. Combined the above miRNAs, a unique serum or plasma expression profile of miR-15b, miR-17, miR-18a, miR-21, miR-23a-3p, miR-24, miR-142-3p, miR-142-5p, miR-195, miR-320a, miR-331, miR376c-3p, miR-423-5p, miR-532, miR-532-3p, miR-652 and miR-1290 could distinguish benign colorectal polyp or adenoma lesions from healthy controls with good accuracy or high AUC values [27][28][29][30][31][32][33]. High levels of circulating miR-34a, miR-152 and low miR-150 levels were associated with the distinguish of patients with polyps or adenomas from those with CRC (AUC from 0.537 to 0.904) [34].…”
Section: Circulating Mirnas In Early Screeningmentioning
confidence: 99%